To expand the expression (3a + 2c)(9a² - 6ac + 4c²), you can use the distributive property.
First, distribute 3a to every term in the second parentheses:
3a * 9a² = 27a³
3a * -6ac = -18a²c
3a * 4c² = 12ac²
Next, distribute 2c to every term in the second parentheses:
2c * 9a² = 18a²c
2c * -6ac = -12ac²
2c * 4c² = 8c³
Now, you have:
27a³ - 18a²c + 12ac² + 18a²c - 12ac² + 8c³
Combine like terms:
27a³ + (-18a²c + 18a²c) + (12ac² - 12ac²) + 8c³
Simplify:
27a³ + 8c³
(3a + 2c)(9a² - 6ac + 4c²)
1 answer